Dominant strategy implementation in economic environments - Hideki Mizukami; Takuma Wakayama (Osaka University, Institute of Social and Economic Research (ISER), 2006)
We study dominant strategy implementation especially in economic environments. We first showthat in general environments, strategy-proofness and quasi-strong-non-bossiness together are necessary and sufficient for dominant strategy implementation via the associated direct revelationmechanism. We next prove that in weak separable environments, strategy-proofness is sufficient for dominant strategy implementation, by using an augmented revelation mechanism similar to the one devised by Jackson et al. (1994). Moreover, we focus on pure exchange economies without free disposal, and try to construct another augmented revelation mechanism that satisfies balancedness in and out of equilibrium, and which implements all strategy-proof social choice functions in dominant strategy equilibria.
Keywords: D51; C72; D71; D78; 330; Augmented Revelation Mechanism; Strategy-Proofness; Balancedness; Quasi-Strong-Non-Bossiness; The Revelation Principle; Spieltheorie; Soziale Wohlfahrtsfunktion; Tauschwirtschaft; Nash-Gleichgewicht; Theorie